The Political Economy of International Organizations - Axel Dreher; Valentin F. Lang (Center for Economic Studies and ifo Institute (CESifo), 2016)
We review the literature on the political economy of international organizations (IOs). Considering IOs as products of the preferences of various actors rather than monolithic entities we focus on national politicians, international bureaucrats, interest groups, and voters. By looking into the details of decision-making in IOs the literature shows that a focus on states as the prime actors in IOs overlooks important facets of the empirical reality. Mainly focusing on empirical research, we structure the paper according to the four main actors involved and examine how they influence, use, and shape IOs. We find that IO behavior often reflects the interests of politicians, bureaucrats, and interest groups, while the impact of voters is limited. The final section discusses proposals for reforms addressing this weak representation of voter preferences.
Keywords: F53; D72; D73; 330; international organizations; public choice; International Monetary Fund; European Union